Strong aftershocks traffic light system: A case study of the 8 January 2022 MS6.9 Menyuan earthquake, Qinghai Province, China - Bi, Jinmeng; Yin, Fengling; Jiang, Changsheng; Yin, Xinxin; Ma, Yong; Song, Cheng (Frontiers in Earth Science, 2023)
Strong aftershocks, especially the disaster-causing M≥5.0 kind, are a key concern for mitigation of seismic risks because they often lead to superimposed earthquake damage. However, the real-time forecasting results of the traditional probability prediction models based on statistics are usually far from accurate and therefore unsatisfactory. Borrowing an idea from the foreshock traffic light system (FTLS), which is based on observations of decreasing b-values or increasing differential stress just before a strong aftershock, we constructed a strong aftershock traffic light system (SATLS) that uses data-driven technology to improve the reliability of time sequence b-value calculations, and analyzed the b-value variations of strong aftershocks in the China continent. We applied this system to the MS6.9 Menyuan earthquake occurred on 8 January 2022. The earthquake occurrence rates before the largest aftershock (MS5.2) forecast by the Omi-R-J model were too low, although the model could accurately forecast aftershock rates for each magnitude interval in most time-periods. However, reliable b-values can be calculated using the time-sequence b-value data-driven (TbDD) method, and the results showed that the b-values continued declining from 1.3 days before the MS5.2 aftershock and gradually recovered afterward. This would suggest that the stress evolution in the focal area can provide data for deciding when to post risk alerts of strong aftershocks. In the process of building the SATLS, we studied thirty-four M≥6.0 intraplate earthquake sequences in the China continent and concluded that the differences between the b-values of the aftershock sequences and of the background events, △b = bafter - bbg = ±0.1, could be used as thresholds to determine whether M≥5.0 aftershocks would occur. The △b value obtained using the events before the MS5.2 aftershock of the MS6.9 Menyuan sequence was about -0.04, which would have caused the SATLS to declare a yellow alert, but there would have been some gap expected before a red alert was triggered by the b-value difference derived from the events associated with this strong aftershock. To accurately forecast a strong aftershock of M≥5.0, a deeper understanding of the true b-value and a detailed description of the stress evolution state in the source area is necessary.